2025年2月4日 星期二

多項式,已知餘數,求商

 GPT Icon

We are given the function:

f(x)=(4x22x+1)(mx+n)+4x9f(x) = (4x^2 - 2x + 1)(mx + n) + 4x - 9

with the conditions:

f(12)=5,f(1)=8.f\left(-\frac{1}{2}\right) = -5, \quad f(1) = -8.

We need to determine mm and nn, and then compute f(2)f(2).


Step 1: Compute f(12)f(-\frac{1}{2})

Substituting x=12x = -\frac{1}{2}:

4(12)22(12)+1=4(14)+1+1=1+1+1=3.4\left(-\frac{1}{2}\right)^2 - 2\left(-\frac{1}{2}\right) + 1 = 4\left(\frac{1}{4}\right) + 1 + 1 = 1 + 1 + 1 = 3.
f(12)=(3)(m(12)+n)+4(12)9f\left(-\frac{1}{2}\right) = (3)(m(-\frac{1}{2}) + n) + 4(-\frac{1}{2}) - 9
=3(m2+n)29= 3\left(-\frac{m}{2} + n\right) - 2 - 9
=3n3m211= 3n - \frac{3m}{2} - 11

Setting this equal to 5-5:

3n3m211=53n - \frac{3m}{2} - 11 = -5
3n3m2=63n - \frac{3m}{2} = 6
3n=3m2+63n = \frac{3m}{2} + 6
n=m2+2n = \frac{m}{2} + 2

Step 2: Compute f(1)f(1)

Substituting x=1x = 1:

4(1)22(1)+1=42+1=3.4(1)^2 - 2(1) + 1 = 4 - 2 + 1 = 3.
f(1)=3(m(1)+n)+4(1)9f(1) = 3(m(1) + n) + 4(1) - 9
=3(m+n)+49= 3(m + n) + 4 - 9
=3m+3n5= 3m + 3n - 5

Setting this equal to 8-8:

3m+3n5=83m + 3n - 5 = -8
3m+3n=33m + 3n = -3
m+n=1m + n = -1

Step 3: Solve for mm and nn

We have the system:

  1. n=m2+2n = \frac{m}{2} + 2
  2. m+n=1m + n = -1

Substituting equation (1) into equation (2):

m+(m2+2)=1m + \left(\frac{m}{2} + 2\right) = -1
m+m2+2=1m + \frac{m}{2} + 2 = -1

Multiply everything by 2 to clear the fraction:

2m+m+4=22m + m + 4 = -2
3m=63m = -6
m=2m = -2

Substituting m=2m = -2 into n=m2+2:

n=22+2=1+2=1n = \frac{-2}{2} + 2 = -1 + 2 = 1

Thus, we have:

m=2,n=1.m = -2, \quad n = 1.

Step 4: Compute f(2)f(2)

Substituting x=2x = 2:

4(2)22(2)+1=164+1=13.4(2)^2 - 2(2) + 1 = 16 - 4 + 1 = 13.
f(2)=(13)(m(2)+n)+4(2)9f(2) = (13)(m(2) + n) + 4(2) - 9
=13(2(2)+1)+89= 13(-2(2) + 1) + 8 - 9
=13(4+1)+89= 13(-4 + 1) + 8 - 9
=13(3)+89= 13(-3) + 8 - 9
=39+89= -39 + 8 - 9
=40= -40

Final Answer

40

多項式,x 位移

 GPT Icon

Yes! Let's perform continuous synthetic division step by step until we get the Nested Division Form of

3x35x27x43x^3 - 5x^2 - 7x - 4

divided by x3.


Step 1: First Synthetic Division

We divide 3x35x27x43x^3 - 5x^2 - 7x - 4 using synthetic division.

Set Up the Synthetic Division Table

  1. Write the coefficients of the polynomial: 3,5,7,43, -5, -7, -4
  2. The divisor is x3x - 3, so we use 3 as the synthetic division factor.
335749121534511\begin{array}{r|rrrr} 3 & 3 & -5 & -7 & -4 \\ & & 9 & 12 & 15 \\ \hline & 3 & 4 & 5 & 11 \\ \end{array}
  • Quotient: 3x2+4x+5
  • Remainder: 1111

Thus, we now divide 3x2+4x+5.


Step 2: Second Synthetic Division

Now, divide 3x2+4x+5.

334593931344\begin{array}{r|rrr} 3 & 3 & 4 & 5 \\ & & 9 & 39 \\ \hline & 3 & 13 & 44 \\ \end{array}
  • Quotient: 3x+13
  • Remainder: 44

Now, divide 3x+133x + 13 by x3x - 3.


Step 3: Third Synthetic Division

Now, divide 3x+133x + 13 by x3.

33139322\begin{array}{r|rr} 3 & 3 & 13 \\ & & 9 \\ \hline & 3 & 22 \\ \end{array}
  • Quotient: 33
  • Remainder: 2222

Step 4: Express in Nested Division Form

Now, we reconstruct the polynomial using the results of the synthetic divisions.

  1. The final quotient is 3.

  2. The previous quotient was 3x+13, which we write as:

    3(x3)+223(x - 3) + 22
  3. The next quotient was 3x2+4x+53x^2 + 4x + 5, which we write using the previous step:

    3(x3)2+22(x3)+443(x - 3)^2 + 22(x - 3) + 44
  4. Finally, including the remainder:

    3(x3)3+22(x3)2+44(x3)+113(x - 3)^3 + 22(x - 3)^2 + 44(x - 3) + 11

Final Answer:

3(x3)3+22(x3)2+44(x3)+11\boxed{3(x - 3)^3 + 22(x - 3)^2 + 44(x - 3) + 11}

This is the Nested Division Form of 3x35x27x43x^3 - 5x^2 - 7x - 4 when divided by x3x - 3.

多項式,替換新變數

 GPT Icon

We are given the equation:

(x23x)214(x23x)+40=0(x^2 - 3x)^2 - 14(x^2 - 3x) + 40 = 0

Step 1: Substituting a New Variable

Let:

y=x23xy = x^2 - 3x

Then, our equation transforms into:

y214y+40=0y^2 - 14y + 40 = 0

Step 2: Solve the Quadratic Equation

The quadratic equation:

y214y+40=0y^2 - 14y + 40 = 0

can be solved using the quadratic formula:

y=(14)±(14)24(1)(40)2(1)y = \frac{-(-14) \pm \sqrt{(-14)^2 - 4(1)(40)}}{2(1)} y=14±1961602y = \frac{14 \pm \sqrt{196 - 160}}{2} y=14±362y = \frac{14 \pm \sqrt{36}}{2} y=14±62y = \frac{14 \pm 6}{2}

Step 3: Find Values of yy

y=14+62=202=10y = \frac{14 + 6}{2} = \frac{20}{2} = 10
y=1462=82=4y = \frac{14 - 6}{2} = \frac{8}{2} = 4

Thus, we have two equations to solve:

x23x=10x^2 - 3x = 10
x23x=4x^2 - 3x = 4

Step 4: Solve for xx

Equation 1: x23x10=0

Factorizing:

(x5)(x+2)=0(x - 5)(x + 2) = 0
x5=0orx+2=0x - 5 = 0 \quad \text{or} \quad x + 2 = 0
x=5orx=2x = 5 \quad \text{or} \quad x = -2

Equation 2: x23x4=0

Factorizing:

(x4)(x+1)=0(x - 4)(x + 1) = 0
x4=0orx+1=0x - 4 = 0 \quad \text{or} \quad x + 1 = 0
x=4orx=1x = 4 \quad \text{or} \quad x = -1

Final Answer

x=5,2,4,1

多項式,求未定係數

 

GPT Icon

Given Equation

2x34x25x+1=a(x1)(x+2)(x+3)+b(x1)(x2)(x3)+c(x+2)(x3)(x+1)2x^3 - 4x^2 - 5x + 1 = a(x - 1)(x + 2)(x + 3) + b(x - 1)(x - 2)(x - 3) + c(x + 2)(x - 3)(x + 1)

We will substitute three specific values of xx to solve for a,b,ca, b, c.


Step 1: Substituting x=1

Since (x1)=0, the terms involving aa and b vanish, leaving:

f(1)=c(1+2)(13)(1+1)f(1) = c(1 + 2)(1 - 3)(1 + 1)

Compute f(1):

2(1)34(1)25(1)+1=245+1=62(1)^3 - 4(1)^2 - 5(1) + 1 = 2 - 4 - 5 + 1 = -6

Compute the right-hand side:

c(3)(2)(2)=12cc(3)(-2)(2) = -12c

Thus, we solve:

6=12c-6 = -12c
c=12c = \frac{1}{2}


Step 2: Substituting x=2

Since (x+2)=0, the terms involving aa and cc vanish, leaving:

f(2)=b(21)(22)(23)f(-2) = b(-2 - 1)(-2 - 2)(-2 - 3)

Compute f(2)f(-2):

2(2)34(2)25(2)+12(-2)^3 - 4(-2)^2 - 5(-2) + 1
=2(8)4(4)5(2)+1= 2(-8) - 4(4) - 5(-2) + 1
=1616+10+1=21= -16 - 16 + 10 + 1 = -21

Compute the right-hand side:

b(3)(4)(5)=60bb(-3)(-4)(-5) = -60b

Thus, we solve:

21=60b-21 = -60b
b=720b = \frac{7}{20}


Step 3: Substituting x=3

Since (x3)=0, the terms involving bb and cc vanish, leaving:

f(3)=a(31)(3+2)(3+3)f(3) = a(3 - 1)(3 + 2)(3 + 3)

Compute f(3)f(3):

2(3)34(3)25(3)+12(3)^3 - 4(3)^2 - 5(3) + 1
=2(27)4(9)15+1= 2(27) - 4(9) - 15 + 1
=543615+1=4= 54 - 36 - 15 + 1 = 4

Compute the right-hand side:

a(2)(5)(6)=60aa(2)(5)(6) = 60a

Thus, we solve:

4=60a4 = 60a
a=115a = \frac{1}{15}


Final Answer

a=115,b=720,c=12\boxed{a = \frac{1}{15}, \quad b = \frac{7}{20}, \quad c = \frac{1}{2}}

This is the correct set of values for a,b,ca, b, c. 😊

表面張力是什麼?它是怎麼形成的?

 請用台灣國小六年級能理解的語言,說明什麼是表面張力?它是怎麼形成的?

ChatGPT 說:
ChatGPT

什麼是表面張力?

表面張力就像是一層看不見的「皮膜」,把水的表面拉緊。想像一下,當你在水面上輕輕放一根針,針雖然比水重,但如果放得很小心,它還是可以浮在水面上,這就是表面張力的效果。

表面張力是怎麼形成的?

水分子之間就像好朋友一樣,會互相拉住對方。在水的內部,每個水分子四周都有其他水分子拉著它,所以它們的力量是平衡的,不會往某個方向移動。

但在水的表面,水分子的上方沒有其他水分子拉住它,只有下面和旁邊的水分子在拉它,這讓水的表面像被拉緊了一樣,就像一張被繃緊的彈簧床一樣,形成一種「皮膜」的感覺。這就是表面張力!

舉個例子:

  • 小昆蟲可以在水面上走,像水黽(ㄇㄧㄣˇ)這種小昆蟲,它們的腳很輕,不會弄破水的表面,所以可以站在水上。
  • 水滴變成圓形,當你看到雨滴時,會發現水滴大多是圓形的,這是因為表面張力讓水收縮成最小的形狀,而球形剛好是最小的表面積的形狀。

這就是表面張力的概念,是水的一種特別的力量!😊